Onshore and offshore wind energy : an introduction - Lynn, Paul A. (Chichester, West Sussex : Wiley, 2012)
'This book uses academic content and rigor to introduce all relevant topics, from global wind resource and historical background, through to modern electricity generation and distribution, including the topical subject area of offshore systems'--
Machine generated contents note: Preface. Acknowledgements. 1. Introduction. 1.1 Wind Energy and Planet Earth. 1.2 Winds of the World. 1.3 From Windmills to Wind Turbines. 1.4 Power, Energy, and Performance. 1.5 Coming up to Date. References. 2. Capturing the Wind. 2.1 Wind Speed and Power. 2.2 Wild Wind. 2.2.1 Introductory. 2.2.2 Wind Statistics. 2.2.3 Mapping and Forecasting. 2.3 Predicting Turbine Output. References. 3. Wind Turbines. 3.1 Turbine Types and Sizes. 3.2 Aerodynamics. 3.2.1 Rotor Efficiency and the Betz Limit. 3.2.2 Lift and Drag. 3.2.3 Rotor Speed. 3.2.4 Rotor Blades. 3.2.4.1 Choosing Airfoils. 3.2.4.2 Stall and Pitch Control. 3.3 Mechanics. 3.3.1 Gearboxes. 3.3.2 Towers. 3.3.3 Vibration and Fatigue. 3.4 Electrics. 3.4.1 AC Electricity. 3.4.2 Generators. 3.4.2.1 Introductory. 3.4.2.2 Synchronous Generators. 3.4.2.3 Asynchronous Generators. 3.4.2.3.1 Squirrel-cage and Wound-rotor Induction Machines. 3.4.2.3.2 Doubly-fed Induction Generators. 3.5 Turbine Control. 3.6 Onshore Wind Farms. 3.6.1 Introductory. 3.6.2 Siting and Spacing. 3.6.3 Monitoring and Control. References. 4. Moving Offshore. 4.1 Introductory. 4.2 Wind and Waves. 4.3 Turbines and Foundations. 4.4 Offshore Wind Farms. 4.4.1 Case Study: Horns Rev 2. 4.4.2 Case Study: London Array. 4.5 Bringing the Power Ashore. References. 5. Grid Integration. 5.1 Setting the Scene. 5.2 Connecting to the Grid. 5.2.1 Grid Strength and Fault Levels. 5.2.2 Electrical Quality. 5.3 Large-scale Wind Power. 5.3.1 Introductory. 5.3.2 Intermittency and Variability. 5.3.3 Capacity Credit and Backup Generation. References. 6. Economics and the Environment. 6.1 Wind Energy Economics. 6.1.1 Capital and Installation Costs. 6.1.2 Operation, Maintenance and Cash Flow. 6.2 Environmental Aspects. 6.2.1 Introductory. 6.2.2 Landscape and Amenity. 6.2.3 Birds, Bats, and Farming. 6.2.4 Seabirds, Fish, and Marine Conservation. References.
Includes bibliographical references and index.
Keywords: Wind power; Offshore electric power plants; Wind energy conversion systems; TECHNOLOGY & ENGINEERING / Power Resources / General